An Integrated Pharmacological Counselling Approach to Guide Decision-Making in the Treatment with CDK4/6 Inhibitors for Metastatic Breast Cancer - Roncato, Rossana; Gerratana, Lorenzo; Palmero, Lorenza; Gagno, Sara; Poetto, Ariana Soledad; Peruzzi, Elena; Zanchetta, Martina; Posocco, Bianca; De Mattia, Elena; Canil, Giovanni; Alberti, Martina; Orleni, Marco; et al. (Frontiers in Pharmacology, 2022)
A wide inter-individual variability in therapeutic response to cyclin-dependent kinases 4 and 6 inhibitors (CDKis) has been reported. We herein present a case series of five patients treated with either palbociclib or ribociclib referred to our clinical pharmacological counselling, including therapeutic drug monitoring (TDM), pharmacogenetics and drug-drug interactions analysis to support clinicians in the management of CDKis treatment for metastatic breast cancer. Patients’ plasma samples for TDM analysis were collected at steady state and analyzed by a LC-MS/MS method for minimum plasma concentration (Cmin) evaluation. Under- and over-exposure to the drug were defined based on the mean Cmin values observed in population pharmacokinetic studies. Polymorphisms in selected genes encoding for proteins involved in drugs absorption, distribution, metabolism, and elimination were analyzed (CYP3A4; CYP3A5; ABCB1, SLCO1B1 and ABCG2). Three of the five reported cases presented a CDKi plasma level above the population mean value and were referred for toxicity. One of them presented a low function ABCB1 haplotype (ABCB1-rs1128503, rs1045642 and rs2032582), possibly causative of both increased drug oral absorption and plasmatic concentration. Two patients resulted underexposed to CDKis and one of them was referred for early progression. In one patient, a CYP3A5*1/*3 genotype was found to be potentially responsible for a more efficient drug metabolism and lower drug plasma concentration. This intensified pharmacological approach in clinical practice was demonstrated to be potentially effective in supporting prescribing oncologists in the process of dose and drug selection and could be ultimately useful to increase both safety and efficacy profile of CDKis treatment.